Intracranial germ-cell tumor with synchronous lesions in the pineal and suprasellar regions: A rare case of hypopituitarism - Ghosh, Kaushik; Bhattacharya, Paromita; Quereshi, Muhammed Imran Ahmad; Mukhopadhyay, Sarmistha; Bhattacharya, Ambarish (Asian Journal of Medical Sciences, 2022)
Germinomas represent the most frequent tumor type in the pineal region and the synchronous involvement in the suprasellar region, known as bifocal disease, is increasingly recognized. Synchronous primary intracranial germ cell tumors are rare. Among all germ cell tumors, only 5–10% are found as synchronous lesions in pineal and suprasellar regions. They are also known by the entity “double mid-line atypical teratoma.” An adolescent male with phenotypic features of delayed puberty presents with features of hypopituitarism and raised intracranial tension. He was subsequently treated with hormonal replacement and diagnosed as a case of bifocal intracranial germinoma. Interestingly, he was lacking features of diabetes insipidus, which is a conspicuous feature in other reported cases. He was treated further with ventricular shunting followed by cranio spinal irradiation. The complex nature of endocrinological manifestations in bifocal intracranial germinoma will enriches our knowledge toward a potentially curable neuroendocrinological situation.